Stability of cupuaçu (Theobroma grandiflorum) nectar during storage - Vieira, M. M. C. (2015)
A shelf-life study on cupua¸cu nectar (Theobroma grandiflorum) was carried out in two parts. Part I studied the microbial stability of the regular nectar (batch R) and the same nectar fortified with synthetic ascorbic acid (AA) (batch F), pasteurized at 90 ◦C for 3 min and hot filled in glass bottles. Total Plate Count (TPC), yeast and molds as well as pH, total soluble solids (TSS), titratable acidity and hidroxymethylfurfural (HMF) were followed along 43 storage days at 4, 25 and 35 ◦C. At the end of the storage period neither TPC nor molds or yeast had recovered the initial loads observed before pasteurization, for both R and F batches. Right after pasteurization, acidity increased slightly, pH decreased from 3.52 to 3.3, and TSS increased from 18.7 to 19.0 ◦Brix, with all stabilizing afterwards. Part II evaluated ascorbic (AA) and dehydroascorbic (DHAA) acids’ stabilization in the two batches, R and F, and dissolved oxygen (DO) was monitored. Both batches were stored at the same temperatures as in Part I for two months. For batch R, the AA degradation results followed a reversible first order reaction (EaAA(R) =-34±6 kJ/mol, k AA(R)25◦C =0.006±0.003 days−1 , C0AA(R)=0.92±0.01 and C ∞AA(R)= 0.43±0.19). For the (F) nectar, the experimental data fitted a first order model well (EaAA(F )=30±17 kJ/mol, k AA(F )25◦C =0.0016±0.0004 days−1 ). DO was modeled as a fractional conversion model (EaDO= 67±17 kJ/mol, kDO25◦C = 1.94±0.94 days−1 , C0DO=0.97±0.03 and C ∞DO= 0.55±0.01). For both nectars, storage at environmental temperatures was preferred (AA retention above 80%) to refrigeration, due to the slower rate of diffusion of DO at lower temperatures.